KEARIFAN LOKAL MASYARAKAT SENTANI, PAPUA, DALAM UNGKAPAN TRADISIONAL - Yektiningtyas, Wigati (Balai Bahasa Jawa Timur, 2017)
The research has an aim of documenting Sentani folklore, especially discussing the existence and functions of Sentani traditional proverbs and seeking to reexplore the values of wisdom they carry within. The proverbs were collected from Sentani region informants by close observation, recordings, interviews, transcription, translation and focus group discussions with the tribal chiefs (ondofolo/khote) as traditional authority holders of Sentani culture. Using the socio-cultural approach, the result shows that the primary values of Sentani wisdom is revealed from the traditional expressions, namely holei narei (build and maintain comradeship), hardwork, mutual cooperation, mutual respect, honesty, and loyalty to traditions that can be used as guidance for (1) education, (2) social life, (3) traditional norms, (4) ethical values, (5) aesthetics (6) economy, and (7) politics.